put the expression for y (first equation) into the second
-2x-3(6x-11)=-7
-2x-18x+33=-7
you take it from there.
HOW TO SOLVE
Y=6X-11
&
-2X-3Y=-7
4 answers
y=6x-11
-2x-3y=-7
-2x-3y=-7
Substitute the value of y from the first equation into the second equation:
-2x - 3(6x - 11) = -7
Simplify and solve for x:
-2x - 18x + 33 = -7
-20x = -40
x = 2
Now substitute the value of x into either equation to find y:
y = 6x - 11
y = 6(2) - 11
y = 1
Therefore, the solution is (2, 1).
-2x - 3(6x - 11) = -7
Simplify and solve for x:
-2x - 18x + 33 = -7
-20x = -40
x = 2
Now substitute the value of x into either equation to find y:
y = 6x - 11
y = 6(2) - 11
y = 1
Therefore, the solution is (2, 1).
Explain how Avery's father in the story "Avery's Gift" is similar to Ellison's father in the article "Chicken of the Sea Is So Wacky--Of Course It Was Created by Kids." In an essay